Pelatihan Peningkatan Kemampuan Ekspresi dan Emosi Melalui Playmate bagi Anak Autis: Training on Improving Expression and Emotion Skills through Playmate for Autistic Children - Sari, Yuli Afmi Ropita; Khalida, Rahmi; Taruna, Rexsy; Suciana, Sri (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Playmate is a mat-shaped game that aims to develop emotional intelligence and accuracy of expression in children. Playmate is an educational medium because it can integrate visual and audio elements that are easily absorbed by autistic children. The problems experienced by partners are emotional and expression problems of autistic clients. Efforts made for partners are empowering parents and teachers in improving the recognition of emotions and expressions of autistic children. The implementation uses the playmate method of colorful expressions and methods that are interesting for autistic children. Autistic children who prefer to be visual. This implementation will be divided into 2, namely providing socialization to teachers and parents. The goal is that when giving treatment to children, it is adjusted to their function at home and school. The results of the service activities are socialization activities attended by all teachers and parents of students. Through these activities, there is an increase in the understanding of teachers and parents in teaching expression and emotion skills in autistic children.